2010
DOI: 10.3109/10242422.2010.528832
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-boosted enzymatic cotton scouring process with cutinase and pectate lyase

Abstract: The synergistic effect between power ultrasound and enzymes in an enzymatic scouring process has been studied. The scouring enzymes were Fusarium solani pisi cutinase (EC 3.1.1.74) and pectate lyase (EC 4.2.2.2). In different stages of the scouring process, power ultrasound with a pre-optimized power of 0.57 W cm(-2) and a frequency of 30 kHz was applied. It was found that ultrasound shortens the enzymatic scouring process time dramatically; less than 5 min was required to achieve the desired scouring expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Hence, mechanical treatment has in some cases been combined with cutinase-catalysed hydrolysis to achieve faster scouring (Agrawal et al 2008(Agrawal et al , 2010. In other cases, non-ionic detergents have been used for more efficient penetration of the enzyme into the cuticle (Degani et al 2002;Lee et al 2010).…”
Section: Use Of Cutinases In Textile Processingmentioning
confidence: 98%
“…Hence, mechanical treatment has in some cases been combined with cutinase-catalysed hydrolysis to achieve faster scouring (Agrawal et al 2008(Agrawal et al , 2010. In other cases, non-ionic detergents have been used for more efficient penetration of the enzyme into the cuticle (Degani et al 2002;Lee et al 2010).…”
Section: Use Of Cutinases In Textile Processingmentioning
confidence: 98%
“…Maximum effects of cavitation for textile treatment (scouring treatment) and wool dyeing were reported at low frequencies, 20-50 kHz [44] and 35-39 kHz [17] respectively. In this work, dosimetry measurements indicate that more active cavitation occurred in the dyeing vessel at a frequency of 400 kHz when compared to other frequencies.…”
Section: The Effect Of Ultrasound Time and Frequency In Hair Morpholomentioning
confidence: 99%
“…Therefore ultrasound can be seen as a source of mechanical energy to accelerate the mass transfer processes in the pores of fabrics. It has been found that ultrasound also accelerates the performance of enzymes in enzymatic textile treatment processes [Agrawal et al & 2010. Figure 5.24 shows the results of some of these experiments.…”
Section: The Application Of Ultrasoundmentioning
confidence: 97%
“…The difference in performance is expressed in Δ % pectin removal. Enzyme concentration without refreshment of the capillary Figure 5.24: Experimentally determined effect of ultrasound on the performance of enzymes [Agrawal et al, 2010] The case was to see the effect of ultrasound on the removal of pectin by the enzyme pectinase. Three experiments have been performed: ultrasound applied before, after and during the enzymatic treatment.…”
Section: The Application Of Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation